Síntese e caracterização de nanopartículas de maghemita associada à dextrana funcionalizada com rodamina B - Jesus, Chelry Fernanda Alves de (2014)
In this study, maghemite nanoparticles associated to dextran were synthesized (crystallites with average diameters of 5.6 and 5.3 nm) from the precipitation of iron salts in an alkaline medium in the presence of dextran of molecular weights of 250 kDa and 75 kDa. Aqueous colloidal dispersions of maghemite/dextran reacted with different amounts of epichlorohydrin aiming at the crosslinking of dextran. The characteristics of the samples were evaluated by X-ray diffraction, high resolution electron microscopy, infrared spectroscopy, thermogravimetric analysis, iron determination, hydrodynamic diameter and zeta potential. One of the maghemite/dextran samples was treated with an ammonium hydroxide solution for different times, seeking the functionalization of dextran with NH2 groups, whose content was determined by potentiometric titration. The maghemite/dextran-NH2 system was conjugated to rhodamine B fluorophore (RodB) under different reaction conditions, being the content of RodB determined by absorption spectrophotometry in the visible region. Photoluminescent characteristics of maghemite/dextran-RodB systems were evaluated by fluorescence microscopy, fluorescence spectrometry and flow cytometry. The results of the analyses and experiments showed that the molecular mass and the crosslinking of dextran did not influence significantly the characteristics of the colloidal systems, since the hydrodynamic diameter values were in the range of 110 and 138 nm and zeta potential was of -4.54 the -10.76 mV. However, the profile of the thermogravimetric curves of the solids was influenced by the crosslinking of dextran, as well as by the presence of the polymer not associated to the nanoparticles. The treatment with ammonia was proved efficient, increasing the number of NH2 groups per particle from 45 to 71. The conjugation of RodB to the maghemite/dextran-NH2 system was more efficient at a pH of 8.5, using a greater amount of carbodiimide and N-hydroxysuccinimide. The maghemite/dextran-RodB system presented different photoluminescent properties according to the content of NH2 groups with in the sample used in the conjugation reaction. The sample treated with the ammonia solution, containing 71 NH2-groups/particle, although it presented less amount of conjugated RodB (2.2 RodB/particle) showed greater fluorescence intensity than the sample showing the highest amount of RodB (2.8 Rod/particle), but that was not treated with ammonia (45-NH2/particle). This result was interpreted considering that the system treated with ammonia favored the RodB conjugation via covalent bond, while the untreated system favored the formation of aggregates of RodB via electrostatic interactions.